An unexpected dual-response pH probe based on acridine. Issue 61 (15th October 2018) - Xu, Liang; Yan, Xiangzhen; Yuan, Chunxue
Abstract : A novel pH fluorescence probe for monitoring extreme acidic and alkaline pH which responds linearly to extreme conditions in the pH ranges of 1.4–3.4 and 12.5–15.0 by utilizing only the acridine moiety. Abstract : A new pH fluorescent probe 2, 8-bis(acridin-9-ylethynyl)-6 H, 12 H -5, 11-methanodibenzo[ b, f ][1, 5]diazocine (TBN ), which has two acridine moieties attached to Tröger's base, is a useful fluorescent probe for monitoring extreme acidic and alkaline pH.TBN displays an excellent pH dependent behavior and responds linearly to extreme conditions in the pH ranges of 1.4–3.4 and 12.5–15.0.TBN can represent a novel type of fluorescent probe with perfect emission properties in extreme acidic and alkaline conditions by utilizing only one functional group.